Effectiveness of foot protectors and forearm guards in Taekwondo - (:unkn) unknown (INT SCIENTIFIC INFORMATION, INC, 2012)
Background and Study Aim: In this study, we evaluated the effectiveness of forearm guards and foot protectors; the forearm and the foot are the main impact targets for kicks in Taekwondo. Material/Methods: We used guards for the forearm (70 g, 16 mm thick) and protectors for the foot dorsum (50 g, 6 mm thick) that were produced from a foam material (Daedo (R)). One load cell (Cas Coop (R)) was fixed on the tip of a swing that performed a pendulum movement. A prosthetic foot was mounted in front of the load cell to mimic the kicking foot. The forearm prosthesis was produced from a hard foam that had natural anthropometric characteristics. Specially designed sensor systems (Tekscan (R), F-Socket system) were mounted on the forearm prosthesis and the prosthetic foot. Using this set-up, the impact on the bare sensors and the impact with both guards mounted on the sensors were measured. The impact parameters recorded were the maximal force, mean force, impulse, maximal pressure, mean pressure and integral pressure. Results: While the total impact force on the load cells without protection was 127.5 +/- 1.18 kg, the forearm guard and foot protection decreased the total impact force to 107.25 +/- 0.52 kg. In addition, the difference between the foot and forearm maximal impact force increased - with protection. For the measured force and pressure parameters, the foot protection had no absorbing effect, in contrast to the forearm guard. Conclusions: Forearm guards used in Taekwondo are more effective than foot protectors.
Keywords: Taekwondo; guards; impact; foot protector; IMPACT FORCE; INJURIES; BLOWS; HEAD; KICK